Impact of early cholecystectomy on the readmission rate in patients with acute gallstone cholangitis: a retrospective single-centre study - Bishnu Sapkota; Gilles Jadd Hoilat; Judie Noemie Hoilat; Ahmed Abu-Zaid; Julia Raleig; Amrenda Mandal; Vanessa Sostre; Christos Carvounis; Joseph Toth (BMJ Open Gastroenterology)
Background and aims The pathogenesis of acute cholangitis (AC) occurs with biliary obstruction followed by bacterial growth in the bile duct. The leading cause of AC is obstructing gallstones. There have been conflicting theories about the optimal timing for cholecystectomy following AC. The aim of this study is to assess the impact of early cholecystectomy on the 30-day readmission rate, 30-day mortality, 90-day readmission rate and the length of hospital stay.Methods This retrospective study was performed between January 2015 and January 2021 in a high-volume tertiary referral teaching hospital. Included patients were 18 years or older with a definitive diagnosis of acute gallstone cholangitis who underwent endoscopic retrograde cholangiopancreatography (ERCP) with complete clearance of the bile duct as an index procedure. We divided the patients into two groups: patients who underwent ERCP alone and those who underwent ERCP with laparoscopic cholecystectomy (LC) on the same admission (ERCP+LC). Data were extracted from electronic medical records. The primary endpoint of the study was the 30-day readmission rate.Results A total of 114 patients with AC met the inclusion criteria of the study. The ERCP+LC group had significantly lower rates of 30-day readmission (2.2% vs 42.6%, p<0.001), 90-day readmission (2.2% vs 30.9%, p<0.001) and 30-day mortality (2.2% vs 16.2%, p=0.017) when compared with the ERCP group. In a multivariate logistic regression analysis, patients in the ERCP+LC group had 90% lower odds of 30-day readmission compared with patients who did not undergo LC during admission (OR=0.1, 95% CI (0.032 to 0.313), p<0.001).Conclusion Performing LC on same day admission was associated with a decrease in 30-day and 90-day readmission rate as well as 30-day mortality.